Effects of Laboratory Teaching Strategy on Academic Performance of Primary School Pupils in Mathematics - Asanre, Akorede; Abiodun, Taiwo (FKIP - Universitas Riau, 2025)
This study looked into how using a laboratory teaching style affected the math performance of elementary school students, in Ijebu Ode, Ogun State, Nigeria. A quantitative study was adopted using Pre-test, Post-test, and Control group quasi-experimental designs. The study involved a total of seventy (70) primary four pupils, separated into two whole groups from separate institutions. We used one class as the experimental group, where the laboratory teaching strategy was implemented and the other class served as the control group, utilizing conventional teaching methods. Mathematics performance tests (r = 0.76) were administered to collect data on academic performance, in addition to carrying out the experimental group's treatment plan and the control group's traditional methods. An analysis of the data was done with ANCOVA, revealing the laboratory teaching technique has a noteworthy favorable impact on students' academic performance. However, gender was found to have not much influence on academic achievement, and likewise, the interaction effect was not significant. The findings bolster the assertion that the laboratory teaching strategy is an effective way to raise primary school pupils' performance in mathematics. As a recommendation, it is suggested that mathematics teachers should be encouraged to integrate this approach into their teaching practices.